Analysing guided and recorded self-generated visual and expressive personal constructs as adjuncts to the counselling process - Jacobs, L.J. (University of Pretoria, 2013)
Dissertation (MEd (Learning Support, Guidance and Counselling))--University of Pretoria, 2005.